Jangka Waktu Yang Diperlukan Pasien Untuk Pelayanan Di Bagian Rawat Jalan Pada Rumah Sakit Pemerintah Di Semarang - Rofi’i, Muhamad; Jarihatunningsih, Sri (Jurnal Manajemen Keperawatan, 2014)
Standard of hospital services is the authority given by government to the hospital to provide maximum services at patients. Service time to the patient affect the level of patient satisfaction. Purpose is to find out the patient service time at the outpatient unit. Survey research methods with quantitative approaches. Population consist of all outpatient both new and old at Hospital in Semarang. Sampling using non probability sampling, specifically purposive sampling. Respondents totaled 108 people. The results showed that the factors affecting the waiting time of service. The total service time of registration less than 10 minutes, as many as 34 (31.48%) and more than 10 minutes as many as 74 (68.52%). Total care clinic less than 30 minutes by 50 (46.29%) and more than 30 minutes were 58 (53.70%). Total pharmacy service time less than 30 minutes by 82 (75.92%) and more than 30 minutes by 26 (24.07%). The total financial service time is less than 5 minutes by 51 (47.22%) and more than 5 minutes total of 57 (52.77%). The results of factor analysis of hospital outpatient services Semarang still need to improve the quality of care by improving the performance of human resource system and better equipment.